Graphene oxide/layered double hydroxide composite as highly efficient and recyclable adsorbent for removal of ciprofloxacin from aqueous phase - Nidhi Sikri; Sandeep Kumar; Bunushree Behera; Jyotsana Mehta (Frontiers in Nanotechnology)
Antibiotics, although developed for curing bacterial infections, contaminate the environment, and their long-term unintentional exposure has detrimental effects on the environment, human health, and other organisms, leading to antibacterial resistance, genotoxicity, birth deformities, inhibition of cell proliferation, and reduction of photosynthetic activity. Therefore, there is a compelling need to remove antibiotic contaminants from water reservoirs, and nano-platforms are emerging as attractive platforms for environmental remediation. In this regard, a composite of graphene oxide (GO) with ZnAlNi layered double hydroxide (LDH) has been explored for highly efficient adsorptive removal of priority antibiotic, ciprofloxacin (CIP). The composite containing ZnAlNi-LDH with specific removal capability towards CIP and GO displaying high surface area for adsorption has been synthesized using the co-precipitation method followed by hydrothermal aging. The formed adsorbent has been structurally characterized using several analytical instrumentation techniques demonstrating its potential for antibiotic adsorption. The adsorption of CIP onto GO-ZnAlNi LDH has been studied by varying several parameters including contact time, pH, adsorbent, and adsorbate concentration. The composite demonstrated more than 80% removal of CIP at 1 mg/L initial concentration from the aqueous solution in 1 h with 10 mg/L adsorbent at pH 7. The kinetics of adsorption fits well with pseudo-first-order model, Elovich model and equilibrium adsorption capacity of 106.97 mg/g was obtained. The composite platform also exhibited high stability, regeneration, and reusability up to five cycles.